2009
DOI: 10.1375/jhtm.16.1.32
|View full text |Cite
|
Sign up to set email alerts
|

A Whole-of-Life Approach to Tourism: The Case for Accessible Tourism Experiences

Abstract: This article examines the concept of a whole-of-life approach to tourism through presenting the case for 'accessible tourism'. The importance of this approach is that it has been estimated that 30% of a population will have access requirements at any point in time, and most people will have a disability at some stage during their life. This article presents the case for proactively developing a strategic accessible tourism approach by presenting a brief background to the area. First, the article outlines the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
196
0
32

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 303 publications
(231 citation statements)
references
References 19 publications
3
196
0
32
Order By: Relevance
“…(Moon, Hart, Komissar & Freidlander, 1995) Importantly, while Universal Design has a clear focus on environmental features its full application in the tourism industry has the potential to contribute significantly to a broad range of socially sustainable outcomes. Baron and Gauntlett (2002) Accessible tourism extends beyond this concept by recognizing a 'whole of life approach' to tourism in which due consideration is given not only across the lifespan through the link between ageing and disability, but also through changing embodiments during lifespan (Darcy & Dickson, 2009). Significantly, a 'whole of life approach' recognizes the inefficiency of enterprises that do not socially accommodate people across the lifespan.…”
Section: Universal Design and Triple Bottom Line Sustainabilitymentioning
confidence: 99%
“…(Moon, Hart, Komissar & Freidlander, 1995) Importantly, while Universal Design has a clear focus on environmental features its full application in the tourism industry has the potential to contribute significantly to a broad range of socially sustainable outcomes. Baron and Gauntlett (2002) Accessible tourism extends beyond this concept by recognizing a 'whole of life approach' to tourism in which due consideration is given not only across the lifespan through the link between ageing and disability, but also through changing embodiments during lifespan (Darcy & Dickson, 2009). Significantly, a 'whole of life approach' recognizes the inefficiency of enterprises that do not socially accommodate people across the lifespan.…”
Section: Universal Design and Triple Bottom Line Sustainabilitymentioning
confidence: 99%
“…olan bireylerin ulaşılabilirlik gereksinimlerinin eşitçe ve bir kişiye bağımlı olmadan (bağımsız bir şekilde) karşılanmasına yönelik evrensel olarak tasarlanmış turistik ürünün, hizmetin ve ortamın sunulmasını ve paydaşlar arasında işbirliği sürecini de içeren bir turizm şeklidir (Darcy & Dickson, 2009;UNWTO, 2013). Turizmde ulaşılabilirlik, turistik ürünün kullanımının önünde engellerin olmaması ile ilgilidir.…”
Section: Bir İhtisaslaşma Modeli: Ulaşılabilir Turizmunclassified
“…Il a pour mission la promotion et la valorisation de la recherche. www.erudit.org People with disabilities, together with family, friends and caregivers, constitute a large potential consumer market segment for the tourism and hospitality industry (Huh and Singh, 2007;Darcy and Dickson, 2009). Government authorities have reported that a considerable number of people have disabilities or are likely to acquire them over the coming decades (Cameron et al, 2010).…”
Section: Résumé De L'articlementioning
confidence: 99%